Age and Growth of Atlantic Sturgeon in the New York Bight. (28th January 2016) - Dunton, Keith J.; Jordaan, Adrian; Secor, David H.; Martinez, Christopher M.; Kehler, Thomas; Hattala, Kathy A.; Van Eenennaam, Joel P.; T. Fisher, Matthew; McKown, Kim A.; Conover, David O.; Frisk, Michael G.
Abstract: Accurate estimates of age and growth of fishes are important in the management and conservation of species and for the development of modeling approaches. Assessments of endangered or rare species typically are limited by poor or inadequate data owing to low abundance, unrepresentative sampling, and/or restrictions on sampling. Atlantic Sturgeon Acipenser oxyrinchus oxyrinchus, which occurs along the east coast of North America, has five distinct population segments (DPSs) listed under the U.S. Endangered Species Act. The New York Bight (NYB) DPS is listed as endangered and represents the largest DPS in the United States. Coastal trawl surveys from 2005 to 2012 were used to evaluate the current age structure of the NYB DPS. A total of 21 year‐classes (mean age = 8.89 years, n = 742 fish) were observed. Age data for the NYB DPS were combined with other available age estimates from multiple research laboratories and sources ( n = 2, 774) in the Hudson River and Delaware River as well from the coastal regions of New York, New Jersey, and Delaware from 1975 to 2012. Collectively, the combined data set captured much of the age range of the species, minimizing age biases and resulting in improved von Bertalanffy parameter estimates ( L ∞ = 278.87, K = 0.057, t 0 = −1.27) with high overall model fit ( r 2 = 0.87). We assessed the effects of individual data sets through a series of leave‐one‐out bootstrap routines that evaluated the influence of each data set on growth parameter estimates. The parameter estimates of the von Bertalanffy growth function were influenced by sampling location and/or researcher effects. Despite these differences, the combined data set approach used here represents the most comprehensive study on the age‐and‐growth relationship of Atlantic Sturgeon and provides parameter estimates for the development of population dynamics models and valuable information for future management. Received February 23, 2015; accepted September 24, 2015